Voluntary Participation and Intergenerational Risk Sharing in a Funded Pension System - Roel Beetsma; Ward Romp; Siert J. Vos (Tinbergen Institute, 2011)
We explore the feasibility of a funded pension system with intergenerational risk sharing when participation in the system is voluntary. Typically, the willingness of the young to participate depends on their belief about the future young's willingness to do so. We characterise equilibria with voluntary participation and show that the likelihood of their existence increases with risk aversion and financial market uncertainty. We find that it is likely that mandatory participation is necessary to sustain a funded pension pillar and to let participants benefit from intergenerational risk sharing.
Keywords: C61; H55; J32; 330; participation constraints; funded pensions; intergenerational risk sharing; Kapitaldeckungsverfahren; Partizipation; Generationengerechtigkeit; Risikopräferenz; Willingness to pay; Overlapping Generations; Theorie